Humanizing Elements of Sufism in India - Sarkar, Ichhimuddin (INSANCITA, 2017)
ABSTRACT: Sufism is no doubt an Islamic way of life to enjoy the blessings of God, which involves vigorous meditation and prayers as well as emphasis on âinner-selfâ rather than external rituals. This paper, by applying the historical method and qualitative study, is intended to analyse the ideology of Sufism and side by side the nature of their activities so as to avoid conflict in the human society as a whole and obviously among the Muslims. The findings show that Islamic mysticism is not separated from Islam and, at the same time, Prophet Muhammad SAW (Salallahu Alaihi Wassalam or peace be upon him) is considered in high esteem in its ideals. The teachings of the Sufi saints are still relevant today, because it invites and elaborates spiritual unity of humanity and above all intra-religious and inter-religious understanding in order to minimize conflict between various creeds and faith holders of India. It is a fact that India is famous for her composite cultural tradition and in the atmosphere of multi-religious as well as multi-lingual society, an idea of mutual co-existence is essential and a vital role was played by the Sufi saints at a moment, when Islam came to India as a new religion and way of life. Love of God in the form of developing a mind to love His creatures became an important theme of common concern of the mystic saints, who came to India and settled in this country in a historical moment. They taught and appealed to the people at large that the Divine discloses itself in the human races as a whole and, thus, they propounded to all the philosophy of love and cordial relationship among human being; and, thereby, to provide means for the betterment of humanity and also to enjoy His blessings.KEY WORD: Islamic Mysticism; Intellectual Currents; Inner-Self; Islamic Humanism; Greater India.Â ABSTRAKSI: âHumanisasi Unsur-unsur Sufisme di Indiaâ. Tasawuf tidak diragukan lagi merupakan cara hidup Islami untuk menikmati berkah Tuhan, yang melibatkan meditasi dan doa penuh semangat serta penekanan pada âbatinâ daripada ritual eksternal. Makalah ini, dengan menerapkan metode historis dan studi kualitatif, dimaksudkan untuk menganalisis ideologi tasawuf dan berdampingan dengan sifat aktivitasnya sehingga dapat menghindari konflik dalam masyarakat manusia secara keseluruhan dan jelasnya di kalangan umat Islam. Temuan menunjukan bahwa mistisisme Islam tidak terpisahkan dari Islam dan, pada saat yang sama, Nabi Muhammad SAW (Salallahu Alaihi Wassalam) dianggap sangat terhormat dalam cita-citanya. Ajaran para Sufi masih relevan saat ini, karena mengundang dan menguraikan kesatuan spiritual umat manusia dan terutama pemahaman intra-agama dan antar-agama untuk meminimalkan konflik antara berbagai keyakinan dan kepercayaan di India. Ini adalah fakta bahwa India terkenal dengan tradisi budayanya yang komposit dan dalam suasana masyarakat multi-agama dan multi-bahasa, gagasan tentang hidup saling berdampingan adalah sangat esensial dan peran penting telah dimainkan oleh orang-orang suci, para Sufi, pada saat itu, ketika Islam datang ke India sebagai sebuah agama dan cara hidup yang baru. Cinta Tuhan dalam bentuk mengembangkan pikiran untuk mencintai ciptaan-Nya merupakan tema penting yang menjadi perhatian bersama orang-orang suci, para mistikus, yang datang ke India dan menetap di negara ini dalam momen yang bersejarah. Mereka mengajarkan dan memohon kepada orang-orang pada umumnya bahwa Tuhan mengungkapkan dirinya dalam ras manusia secara keseluruhan dan, karenanya, mereka mengemukakan bahwa semua filosofi cinta dan perlunya hubungan baik antara manusia; dan, dengan demikian, untuk menyediakan sarana bagi kemajuan kemanusiaan dan juga untuk menikmati berkah-Nya.KATA KUNCI: Mistisisme Islam; Arus Intelektual; Batin; Humanisme Islam; India Besar.About the Author: Professor Ichhimuddin Sarkar is a Lecturer at the Department of History, University of North Bengal, India. For academic interests, the author is able to be contacted via his e-mail address at: isarkar_nbu@yahoo.comSuggested Citation: Sarkar, Ichhimuddin. (2017). âHumanizing Elements of Sufism in Indiaâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Volume 2(2), August, pp.71-82. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 2443-1776. Article Timeline: Accepted (April 7, 2017); Revised (June 17, 2017); and Published (August 30, 2017).